2014
DOI: 10.18097/pbmc20146003281
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of human blood

Abstract: Metabolomics is a novel “omics” branch of science intended for studying a comprehensive set of low molecular weight substances (metabolites) of various biological objects. Metabolite profiles represent a molecular phenotype of biological systems and reflect information encoded at the genome level and realized at the transcriptome and proteome levels. Analysis of human blood metabolic profile is universal and promising tool for clinical applications because it is a sensitive measure of both endogenous and exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 49 publications
2
12
0
1
Order By: Relevance
“…Similar results have been reported in other studies which applied the AHP method for groundwater potential zonation [4,140,141]. According to the AUC value obtained, the GIS-based AHP model's prediction accuracy could be accepted as satisfactory (0.6-0.7) [142]. However, this result can be improved by adding more wells, flow rates, and depth data.…”
Section: Validation Of Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results have been reported in other studies which applied the AHP method for groundwater potential zonation [4,140,141]. According to the AUC value obtained, the GIS-based AHP model's prediction accuracy could be accepted as satisfactory (0.6-0.7) [142]. However, this result can be improved by adding more wells, flow rates, and depth data.…”
Section: Validation Of Resultssupporting
confidence: 85%
“…In this study, freshwater potential zones in the SLPB were identified and analyzed with remote sensing, GIS, and Analytic Hierarchy Process (AHP) using seven thematic layers such as geology, lineament density, LULC, TWI, rainfall, drainage density, and Similar results have been reported in other studies which applied the AHP method for groundwater potential zonation [4,140,141]. According to the AUC value obtained, the GISbased AHP model's prediction accuracy could be accepted as satisfactory (0.6-0.7) [142]. However, this result can be improved by adding more wells, flow rates, and depth data.…”
Section: Discussionsupporting
confidence: 61%
“…The developed LDT is based on direct mass spectrometry of blood plasma, which has been widely used in metabolomics and, in particular, in the laboratory where LDTs were developed for the study of cancers [ 28 , 29 , 30 , 31 , 32 ], diabetes [ 33 ], and PD [ 34 ]. This type of mass spectrometry is characterized by a high processing speed and a relatively high reproducibility [ 35 , 36 , 37 ], which are important for the use of mass spectrometry in the clinic. The mass spectrometry data processing, like peak alignment and data standardization, was specially developed for high-resolution mass spectra and successfully used for many years in studies of blood plasma [ 29 , 38 ] and now is implemented in the LDT.…”
Section: Discussionmentioning
confidence: 99%
“…Кровьосновной переносчик низкомолекулярных веществ в организме, являющихся питательными веществами, гормонами, субстратами и продуктами биохимических реакций. Кровь омывает все ткани в организме, и в неё выделяются вещества в ответ на внешние или внутренние стимулы [19]. Метаболомные исследования проводят методом ЯМР-спектроскопии и масс-спектрометрии [20][21][22][23].…”
Section: происхождение метаболомного анализа кровиunclassified